Plasticity of the C15-CaAl2 Laves phase at room temperature. (January 2023) - Freund, M.; Andre, D.; Sun, P.L.; Kusche, C.F.; Sandlöbes-Haut, S.; Springer, H.; Korte-Kerzel, S.
Graphical abstract: Highlights: We find that the 1 1 2 plane seems to be dominant for plasticity, although previous literature lists deformation on the 1 1 1 plane as the dominant mechanism for C15 Laves phases. We could quantify the CRSS for both slip systems, namely 111 〈 1 1 ¯ 0 〉 and 112 〈 1 1 ¯ 0 〉, as approximately the same at ∼ 1 GPa. Our TEM investigations confirm the [ 1 1 ¯ 0 ] Burgers vector type by using the g∙b analysis. Together, these insights also allow us to explain why the crack and slip trace distribution around indentations varies systematically with crystal orientation. Abstract: The room temperature plasticity of the cubic C15 CaAl2 Laves phase was investigated using nanomechanical testing and electron microscopy. The correlation between slip traces in the vicinity of nanoindents and crystallographic orientation data allowed us to gain statistical data on the activated slip and crack planes for 10 different crystallographic orientations. Slip on 1 1 1 and 1 1 2 planes was found to be most favourable for all orientations, whereas cracks predominantly occurred on 1 1 2 planes. A constant hardness of 4.9 ± 0.7 GPa and an indentation modulus of 85.5 ± 4.0 GPa for all investigated orientations for a constant strain rate and a strain rate sensitivity of 0.028 ± 0.019 were measured. Micropillar compression tests and transmission electron microscopy confirmed slip on 1 1 1 and 1 1 2 planes with a Burgers vector of < 1 1 ¯ 0 > type. This allowed to determine the critical resolved shear stresses as 0.99 ± 0.03 GPa for 1 1 1< 1 1 ¯ 0 > and 0.97 ± 0.07 GPa for 1 1 2< 1 1 ¯ 0 > slip.